Strategi Pengelolaan Kelas Dalam Meningkatkan Efektivitas Pembelajaran Anak Kelompok B TK PGRI RA Kartini Lajulor Singgahan Tuban Tahun Pelajaran 2021/2022 - Novitasari, Nurul (Institut Agama Islam Negeri Ponorogo, 2022)
This article aims to explain classroom management strategies in improving student learning in group B TK PGRI RA Kartini Lajulor Singgahan Tuban. In this research, the researcher uses a qualitative case study approach and is descriptive in nature. This research uses interview, observation, and documentation methods. There were 3 informants in this qualitative research, namely: the head of the Kindergarten, the class teacher in group B, and the guardians of students in group B. Data analysis used 3 stages, namely: data reduction, data display, and drawing conclusions. First, class management for group B students of TK PGRI RA Kartini Lajulor Singgahan Tuban is carried out by referring to the process of planning, organizing, leading and supervising. Second, the effectiveness of learning applied to group B students of TK PGRI RA Kartini Lajulor Singgahan Tuban is the activeness and skills of students that involve both physically and mentally, using various learning methods, teaching teacher motivation in class, creating democratic learning conditions in the classroom, and conducive learning interactions. Third, the strategy used to increase the effectiveness of group B student learning at TK PGRI RA Kartini Lajulor Singgahan Tuban, namely learning that links students to be active, seeks to encourage student interest and attention to learning, motivates student learning enthusiasm, adequate student services, improves teaching skills, conducting discussions on learning difficulties, and creating educational infrastructure in stages.